Tinjauan tentang Teknologi dan Pembaruan Pendidikan Di Era Pengetahuan - Imas Cintamulya (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
The 21st Century is an era of knowledge because knowledge becomes the main foundation of all aspects of life. Knowledge era is an era with the demands of a more complex and challenging, where this era of enormous influence on education. Therefore, education is faced with the challenge to produce quality human resources in meeting the challenges and demands of a competitive nature. For that skills such as acting and thinking critically, creatively, work collaboratively, cross-cultural understanding, communication, computer controlled, career and learning to accept required on this knowledge era. Entering the era of knowledge, education in Indonesia is preparing for the educational system in order to prepare skilled and skilled labor needed in the process of industrialization, and foster and develop a mastery of the various branches of science and technology expertise. Another thing that needs to be prepared are the educators are flexible in the profession